(untitled) (Eurasian Scientific Herald, 2024)
This article discusses the use of movement games as a tool of physical education to develop physical qualities in preschool children. It identifies the theoretical foundations and methodological approaches to enhance movement activities in preschool institutions. The study also examines the organization of physical education and public health activities aimed at improving the physical activity of children in the context of preschool education.